Outcomes in AB0 Incompatible Living Donor Kidney Transplantation: A Case – Control Study - Cozzi, Martina; Donato, Paola; Ugolini, Gabriele; Nguefouet Momo, Rostand Emmanuel; Nacchia, Francesco; Ballarini, Zeno; Piccoli, Pierluigi; Cantini, Maurizio; Caletti, Chiara; Andreola, Stefano; Gandini, Giorgio; Gambaro, Giovanni; et al. (Frontiers in Medicine, 2022)
Background Patients waiting for a kidney transplant by far exceed available organs. AB0 incompatible living donor kidney transplantation (AB0i LDKT) represents an additional therapeutic strategy, but with higher risk for complications. We aimed at evaluating outcomes of AB0i LDKTs compared to compatible (AB0c) controls at our Institution. Methods Retrospective matched case – control study (1:2) comparing AB0i vs. AB0c LDKTs from March 2012 to September 2021. Considered outcomes: graft function, acute rejection, sepsis, CMV infection, BK virus reactivation, death-censored graft survival, patient survival. Results Seventeen AB0i LDKTs matched to 34 AB0c controls. We found excellent graft function, comparable in the two groups, at all considered intervals, with an eGFR (ml/min/1.73 m2) of 67 vs. 66 at 1 year (p = 0.41), 63 vs. 64 at 3 years (p = 0.53). AB0i recipients had a statistically significant higher incidence of acute rejection, acute antibody-mediated rejection and sepsis within 30 days (p = 0.016; p = 0.02; p = 0.001), 1 year (p = 0.012; p = 0.02; p = 0.0004) and 3 years (p = 0.004; p = 0.006; p = 0.012) after surgery. There was no difference in CMV infection, BK virus reactivation, death-censored graft survival between the two groups. Patient survival was inferior in AB0i group at 1 and 3 years (88.2 vs. 100%; log-rank p = 0.03) due to early death for opportunistic infections. AB0i LDKTs spent longer time on dialysis (p = 0.04) and 82.3 vs. 38.3% controls had blood group 0 (p = 0.003). Conclusions AB0i LDKT is an effective therapeutic strategy with graft function and survival comparable to AB0c LDKTs, despite higher rates of acute rejection and sepsis. It is an additional opportunity for patients with less chances of being transplanted, as blood group 0 individuals.